2018
DOI: 10.1186/s12889-018-5341-9
|View full text |Cite
|
Sign up to set email alerts
|

Mass media and risk factors for cancer: the under-representation of age

Abstract: BackgroundIncreasing age is a risk factor for developing cancer. Yet, older people commonly underestimate this risk, are less likely to be aware of the early symptoms, and are more likely to be diagnosed with advanced stage cancer. Mass media are a key influence on the public’s understanding health issues, including cancer risk. This study investigates how news media have represented age and other risk factors in the most common cancers over time.MethodsEight hundred articles about the four most common cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
0
18
0
1
Order By: Relevance
“…One can mitigate the risk of contracting the disease, and hence be less contagious, by taking the necessary precautionary measures; however, this idea that adverse outcomes only happen to others stems from the human psyche. Previous studies across different domains have shown that people generally tend to be optimistic regarding their health and usually underestimate their own risk of suffering from diseases or health-related negative outcomes (20,21). This could be one of the explanations for why almost half of our sample believed they were able to avoid contracting COVID-19.…”
Section: Discussionmentioning
confidence: 80%
“…One can mitigate the risk of contracting the disease, and hence be less contagious, by taking the necessary precautionary measures; however, this idea that adverse outcomes only happen to others stems from the human psyche. Previous studies across different domains have shown that people generally tend to be optimistic regarding their health and usually underestimate their own risk of suffering from diseases or health-related negative outcomes (20,21). This could be one of the explanations for why almost half of our sample believed they were able to avoid contracting COVID-19.…”
Section: Discussionmentioning
confidence: 80%
“…This result may suggest that a similar reach can be achieved with a mass media campaign of a shorter duration. Mass media campaigns do not appear to reach older participants, perhaps, because people aged over 60 years old feature rarely in such campaigns [21] including the BCAC. The BCAC found it a challenge to recruit older survivors to share their stories on TV or online.…”
Section: Discussionmentioning
confidence: 99%
“…Guided by past media and social media research (e.g. O'Hanlon, 2019; Macdonald et al, 2018;Chou et al, 2011) and the particular aim of the current study, the researcher developed six selection criteria to guide the blog selection process: i) Location of the bloggers -Malaysia; ii) Types of narrative -first-person narrative, iii) Language -predominantly written in English with minimal use of Malay language; iv) Focus of the blogs -experience coping with the physical and psychological effects of breast cancer iv) Blog privacy setting -publicly available; v) Blog posting -actively written for at least a year and contain an adequate amount of information on BC survivors' experience with a minimum of thirty blog postings and; vi) Blog hits -more than 5,000 hits.…”
Section: Methodology Data Collection Proceduresmentioning
confidence: 99%
“…Media representations in relation to cancer discourse are important because representations shape people's beliefs on health and illness, demonstrate the associated behaviours and shared experiences of cancer patients (Macdonald et al, 2018;Castillo, Godoy-Izquierdo, Vázquez, & Godoy, 2011;Hodgetts & Chamberlain, 2006;Lyons, 2000). Thus, exploring media and its association with illness discourse (i.e.…”
Section: Introductionmentioning
confidence: 99%